The Prevalence of Urogenital Infections in Pregnant Women Experiencing Preterm and Full-Term Labor - Paulo César Giraldo; Edilson D. Araújo; José Eleutério Junior; Rose Luce Gomes do Amaral; Mauro R. L. Passos; Ana Katherine Gonçalves (Hindawi Limited, 2012)
Urogenital infections are extremely prevalent during pregnancy and are an important cause of premature labor. However, the prevalence of urogenital infections during childbirth is not well known. Objective. Identify urogenital infections present at the beginning of labor in both full-term and preterm pregnancies. Study Design. Ninety-four women were admitted to the inpatient maternity clinic of the Federal University of Rio Grande do Norte (UFRN). In total, 49 women in preterm labor and 45 women in full-term labor were included in the study, and samples of urinary, vaginal, and perianal material were collected for microbiological analysis. Results. The prevalences of general infections in the preterm labor group and the full-term labor group were 49.0% and 53.3% (P=0.8300), respectively. Urogenital infections in the preterm and full-term labor groups included urinary tract infection in 36.7% and 22.2% of women, vaginal candidiasis in 20.4% and 28.9% of women, bacterial vaginosis in 34.7% and 28.9% of women, and group B streptococcus in 6.1% and 15.6% of women, respectively. Conclusions. Urogenital infections were prevalent in women in preterm labor and full-term labor; however, significant differences between the groups were not observed.